2019
DOI: 10.1016/j.stem.2019.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Restores CNS Remyelination Capacity by Rejuvenating Aged Stem Cells

Abstract: SummaryThe age-related failure to produce oligodendrocytes from oligodendrocyte progenitor cells (OPCs) is associated with irreversible neurodegeneration in multiple sclerosis (MS). Consequently, regenerative approaches have significant potential for treating chronic demyelinating diseases. Here, we show that the differentiation potential of adult rodent OPCs decreases with age. Aged OPCs become unresponsive to pro-differentiation signals, suggesting intrinsic constraints on therapeutic approaches aimed at enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
315
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 298 publications
(357 citation statements)
references
References 57 publications
21
315
0
Order By: Relevance
“…The inability to recover fully from a demyelinating event raises the possibility that inflammation persists long after the initial trauma, or that OPCs in these regions are permanently altered as a result of exposure to this environment, if only for a short time (Baxi et al, 2015; Kirby et al, 2019). Like other progenitor cells, OPCs exhibit a decline in regenerative potential with age and can undergo senescence, a process that may be accelerated by exposure to inflammatory cytokines (Kirby et al, 2019; Neumann et al, 2019; Nicaise et al, 2019). It is also possible that there is a restricted time period during which OPCs can detect and respond to myelin loss; if there are inherent limits on OPC mobilization, as suggested by the uniform behavior of OPCs across cortical layers, then the inability to match the demand for new cells early may lead to prolonged deficits.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to recover fully from a demyelinating event raises the possibility that inflammation persists long after the initial trauma, or that OPCs in these regions are permanently altered as a result of exposure to this environment, if only for a short time (Baxi et al, 2015; Kirby et al, 2019). Like other progenitor cells, OPCs exhibit a decline in regenerative potential with age and can undergo senescence, a process that may be accelerated by exposure to inflammatory cytokines (Kirby et al, 2019; Neumann et al, 2019; Nicaise et al, 2019). It is also possible that there is a restricted time period during which OPCs can detect and respond to myelin loss; if there are inherent limits on OPC mobilization, as suggested by the uniform behavior of OPCs across cortical layers, then the inability to match the demand for new cells early may lead to prolonged deficits.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in OPC density, resulting from the block of proliferation, could hypothetically have also contributed to differentiation failure. However, we have recently shown that halving the cellular density per well, does not alter differentiation capacity of OPCs (Neumann et al, 2019). Together, our data suggest that proliferation is directly linked and required for differentiation in vitro and during remyelination in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…A prevalent hypothesis to explain the decline in remyelination efficiency with age is a failure of OPCs to differentiate into mature oligodendrocytes in a timely fashion (Boda et al, 2015; Shen et al, 2008; Woodruff et al, 2004). Recently, we have shown that the exposure of aged OPCs to differentiation-enhancing compounds cannot enhance their differentiation, suggesting that aged OPCs cannot respond to differentiation signals (Neumann et al, 2019). Our finding that OPCs must undergo proliferation to differentiate might offer an intriguing explanation for this observation since aged OPCs have a markedly reduced capacity to proliferate both in vitro and in vivo (Ruckh et al, 2012; Segel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations